A taxonomic review on the katydids of the genus Anthracites Redtenbacher, 1891 (Tettigoniidae: Conocephalinae: Agraeciini) from Mindanao, Philippines - Sabang, Aira Mae M.; Bahoy, Daphne Cayle M.; Grumo, Kim C.; Gono, Alfredo Iii A.; Salvador, Jewel Anne G.; Rivera, Rodrin R.; Nuñeza, Olga Macas; Robillard, Tony; Tan, Ming Kai (Zootaxa, 2024)
Anthracites Redtenbacher, 1891 is a genus of Agraeciini with 13 species, of which 11 are found in the Philippines. In the Philippines, seven species were described from Mindanao, the most among other main islands. Based on recently collected material from different parts of Mindanao, we describe two additional new species: Anthracites alatus Tan, Bahoy & Sabang sp. nov. from Mount Balatukan in Misamis Oriental, and Anthracites sebu Tan, Bahoy & Sabang sp. nov. from Lake Sebu in South Cotabato. We also describe the previously-unknown males of Anthracites geniculatus Dohrn, 1905 and Anthracites pyramidalis Ingrisch, 2015. We also report new locality records for Anthracites flagellatus Ingrisch, 2015 on Mount Balatukan, Anthracites geniculatus in Surigao del Sur, Anthracites pyramidalis from Lake Sebu in South Cotabato, and Anthracites zebra Hebard, 1922 on Mount Malindang.